2013
DOI: 10.1055/s-0033-1333661
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Its Role in Training

Abstract: Despite its short history, surgical simulation has been successfully introduced into surgical residency programs in an effort to augment training. A wide range of simulator types and levels of complexity have proven an effective teaching method for surgical trainees. They have been used for training in areas such as general surgery, urology, gynecology, and ophthalmology among others. Coincident with the introduction of simulators is the need for objective evaluation of skills learned on them, which has led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 73 publications
(73 reference statements)
0
57
0
Order By: Relevance
“…Training surgeons is expensive, time‐consuming and often relies on skill acquisition along a learning curve that involves a high volume of cases with expert supervision. Advances in simulation and immersive technologies may address these challenges by providing a safe and scalable training environment. A study from Rwanda confirmed the feasibility of simulation‐based training to improve operative skills when delivered as a brief training intervention in LMICs.…”
Section: Exemplarsmentioning
confidence: 99%
“…Training surgeons is expensive, time‐consuming and often relies on skill acquisition along a learning curve that involves a high volume of cases with expert supervision. Advances in simulation and immersive technologies may address these challenges by providing a safe and scalable training environment. A study from Rwanda confirmed the feasibility of simulation‐based training to improve operative skills when delivered as a brief training intervention in LMICs.…”
Section: Exemplarsmentioning
confidence: 99%
“…Face validity is assessed informally by nonexperts and is used to determine the realism of a simulator, or whether the simulator represents what it is supposed to represent. 33 2. Content validity is the assessment of the appropriateness of a simulator as a teaching modality and involves formal evaluation by experts.…”
Section: Simulation Validity -Metricsmentioning
confidence: 99%
“…Many types of simulators of varying complexity have been developed and marketed. The existing simulators can be divided into three groups: virtual reality (VR) simulators, physical simulators, and hybrid simulators .…”
Section: Introductionmentioning
confidence: 99%